Smart Colloidal Materials
DOI: 10.1007/2882_050
|View full text |Cite
|
Sign up to set email alerts
|

Responsive Giant Vesicles Filled with Poly(N-isopropylacrylamide) Sols or Gels

Abstract: We prepared giant unilamellar vesicles (GUVs) enclosing solutions or covalent gels of Poly(Nisopropylacrylamide) (PolyNipam). Concentrated suspensions of GUVs were prepared by applying an alternative field on a lipid film hydrated by a monomer solution containing N-isopropylacrylamide, crosslinker (N,N'-methylene-bis-acrylamide), initiator and sucrose. Vesicle inner medium was polymerised and cross-linked by U.V.irradiation of the suspension, yielding viscous vesicles enclosing a solution of linear PolyNipam c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
3
9
0
Order By: Relevance
“…In previous studies, 9,12 GUVs filled with a poly(NIPAM) gel were shown to also undergo a significant volume change around 32.5 C. The deswelling ratio a ¼ V/V 0 , where V 0 is the gel volume at room temperature and V the volume after collapse, was in good agreement with experiments on comparable macroscopic gels. 11 Furthermore, a was found to be independant of the vesicle size, revealing no effect of the confinement inside the vesicles.…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…In previous studies, 9,12 GUVs filled with a poly(NIPAM) gel were shown to also undergo a significant volume change around 32.5 C. The deswelling ratio a ¼ V/V 0 , where V 0 is the gel volume at room temperature and V the volume after collapse, was in good agreement with experiments on comparable macroscopic gels. 11 Furthermore, a was found to be independant of the vesicle size, revealing no effect of the confinement inside the vesicles.…”
Section: Introductionsupporting
confidence: 79%
“…3 row (b), we observe local demixing of the poly(NIPAM) chains for the GUVs prepared with F NIPAM ¼ 0.03 and 0.06, as has been already reported. 9,12,16 As expected, the internal medium of the vesicle flickers because of the concentration heterogeneities associated with the frustrated phase transition, but the radius of the vesicle remains constant. The behaviour observed in the case of the vesicle prepared with a volume fraction F NIPAM ¼ 0.07 is dramatically different.…”
Section: Influence Of the Internal Polymer Concentration On The Volum...supporting
confidence: 65%
See 2 more Smart Citations
“…The most developed approach using polymers, especially by Viallat and coworkers, consists in encapsulating a poly(N-isopropylacrylamide) (PNIPAAm)-based solution in liposomes, which will in situ polymerize upon photoactivation into covalently crosslinked gels. [48][49][50][51][52][53][54] Jesorka, Orwar and coworkers reported other important contributions to the field using viscous solutions of non-crosslinked PNIPAAm that were microinjected in liposomes. Reversible sol-gel transitions were observed by heating above LCST, 55 and by doing so in the presence of poly-(acrylic acid) PAA, poly(sodium 4-styrene sulfonate) PSS and 2 000 000 g mol À1 dextran.…”
Section: Compartments With a Gel Lumen: Mimicking The Cytoskeleton In...mentioning
confidence: 99%